[beta]-Glucan Synthesis in the Cotton Fiber (III. Identification of UDP-Glucose-Binding Subunits of [beta]-Glucan Synthases by Photoaffinity Labeling with [[beta]-32P]5[prime]-N3-UDP-Glucose. - Li, L. (1993)
Using differential product entrapment and photolabeling under specifying conditions, we identifIed a 37-kD polypeptide as the best candidate among the UDP-glucose-binding polypeptides for the catalytic subunit of cotton (Gossypium hirsutum) cellulose synthase. This polypeptide is enriched by entrapment under conditions favoring [beta]-1,4-glucan synthesis, and it is magnesium dependent and sensitive to unlabeled UDP-glucose. A 52-kD polypeptide was identified as the most likely candidate for the catalytic subunit of [beta]-1,3-glucan synthase because this polypeptide is the most abundant protein in the entrapment fraction obtained under conditions favoring [beta]-1,3-glucan synthesis, is coincident with [beta]-1,3-glucan synthase activity, and is calcium dependent. The possible involvement of other polypeptides in the synthesis of [beta]-1,3-glucan is discussed.